Lived experiences of two pre-service teachers from a midwestern rural university during internships - Splichal, Kevin L. (Kansas State University, 2015)
This phenomenological study explores the lived experiences of two elementary pre-service teachers in a Mid-western rural university in an attempt to heighten the quality and depth of those experiences as they pertain to pre-service teacher preparation prior to student teaching. The study analyzed the pre-service teachers’ descriptions of their lived experiences in elementary schools during internship experiences and how those experiences contributed to their personal growth as educators. Flick’s (2009) recommendations for phenomenological data analysis of personal journals and face-to-face interviews was used as a methodological framework for exploration of the two pre-service teachers’ lived experiences while Van Manen’s (1990) journal and interview methodologies were used for data collection. The findings were represented in thematic format and revealed transformational learning experiences for both participants. The six phenomenological themes captured the essences of teacher and student relationships and how classroom experiences contributed to personal learning opportunities for the pre-service teachers. Moreover, the findings of this study bolstered the necessity for pre-service teachers to reflect upon and evaluate interpersonal and intrapersonal lived experiences as they relate to the basic tenets of phenomenology in order to gain a fuller appreciation for how lived experiences of pre-service teachers, and their students, contribute to professional growth and improved decision-making skills. This study argues for a more attuned investigation of the basic tenets of phenomenology to increase student achievement through improved teacher and student relationships, and to enhance pre-service teachers’ personal and professional learning.
Keywords: Pre-service teachers; Clinical based practices; Internships; Internship experiences; Phenomenology; Lived experiences; Curriculum Development (0727); Educational leadership (0449); Elementary Education (0524)